STRATEGI PENGEMBANGAN USAHA MIKRO DAN PEMBANGUNAN EKONOMI DESA DI DESA BADERAN KECAMATAN GENENG KABUPATEN NGAWI - endang endang murti (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
The objectives of this study were (1) to determine the strategy for developing micro-enterprises in Baderan Village, Geneng District, Ngawi Regency; (2) To find out the economic development of the village in Baderan Village, Geneng District, Ngawi Regency; and (3) To find out the inhibiting factors for micro-enterprise development and village economic development in Baderan Village, Geneng District, Ngawi Regency. This research is a quantitative descriptive study, the data obtained from the sample of the research population were analyzed according to the statistical method used and then interpreted. The purpose of this study was to determine the strategy of developing micro-enterprises, in order to improve the economy of rural communities in Baderan Village, Geneng District, Ngawi Regency. The population in the study was 50 people, which included (1) employees of the Department of Cooperatives and Micro Enterprises in Ngawi Regency as many as 12 people; (2) The Village Head and Baderan Village apparatus are 1 person and (3) Micro business actors in Baderan Village are 37 people. Data collection techniques in this study used a questionnaire, documentation and observation. While the data analysis in this study used descriptive analysis. Based on the analysis and interpretation of the data, the authors can convey the conclusions of the research results as follows: (1) The Strategy for Development of Micro, Small and Medium Enterprises in Baderan Village, Geneng District, Ngawi Regency is quite good; (2) Improvement of the Rural Economy in Baderan Village, Geneng District, Ngawi Regency is good; and (3) Inhibiting factors for the development of micro, small and medium enterprises and in Baderan Village include the low management capability of business actors. The research findings also show that the Department of Cooperatives and Micro Enterprises in Ngawi Regency has never provided guidance and training in improving management skills for Micro Enterprises in Baderan Village, Geneng District, Ngawi Regency. While the inhibiting factors for village economic development in Baderan Village, among others, are the quality of human resources, access to information and the low level of income of the population. Access to information obtained by the people of Baderan Village is still lacking in both quality and quantity. Access to information from various parties obtained by the people of Baderan Village, Geneng District, Ngawi Regency has good quality, but there are still some people who do not have good quality access to information. The quality of human resources in Baderan Village is still relatively low.